Performance evaluation of 5G cellular vehicle networks - Jun WANG; Xiaodong JI; Xinran ZHANG; Xiaoran WEN; Jiajun TONG (Dianxin kexue)
Cellular vehicle networks (C-V2X) is one of the key technologies of intelligent transportation systems.Ve-hicles exchange information with surrounding information entities in real time to ensure traffic safety and improve traffic efficiency,which meets the basic demands of V2X communication.Besides,it will be applied to automatic driving,assisting driving and other advanced scenarios in the NR-V2X scene.5G-V2X system-level simulation plat-form was developed through opnet.For different application scenarios,coverage performance of 5G C-V2X was analyzed based on simulation results,and suggestions for improvement were given,which has important directive to production practices for the research and system deployment of 5G-V2X.